2016
DOI: 10.3892/etm.2016.3482
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the esophagus treated by endoscopic submucosal dissection: A case report

Abstract: Primary malignant melanoma of the esophagus (PMME) is a rare malignant neoplasm of the esophagus. In the majority of cases, the disease originates in the mucosal layer of the esophagus, which is similar to other types of esophageal cancer. With the development of endoscopic submucosal dissection (ESD), endoscopic resection is possible for cases in which melanomas are limited to the mucosal and submucosal layer. However, few studies report the efficiency of ESD for PMME, and no studies perform long-term follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Immune checkpoint inhibitors, such as anti-CTLA-4 and anti-PD-1 antibodies, provide survival benefits for patients with advanced malignant melanoma. [34][35][36] A review of the literature revealed that only three patients with PMME have received immune checkpoint inhibitors, two have received ipilimumab therapy, 37,38 and one patient has received nivolumab. 21 In the present study, the patient who was PMME is a considerably aggressive tumor with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors, such as anti-CTLA-4 and anti-PD-1 antibodies, provide survival benefits for patients with advanced malignant melanoma. [34][35][36] A review of the literature revealed that only three patients with PMME have received immune checkpoint inhibitors, two have received ipilimumab therapy, 37,38 and one patient has received nivolumab. 21 In the present study, the patient who was PMME is a considerably aggressive tumor with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic resection for early‐stage PMME has not been well established. However, as described in previous reports, EGD plays an important role in the early detection of PMME …”
Section: Discussionmentioning
confidence: 78%
“…However, as described in previous reports, EGD plays an important role in the early detection of PMME. 7 About 90% of PMME is located in the middle or lower third of the esophagus, 8 and the typical endoscopic finding is a pigmented polypoid tumor that is rarely accompanied with ulcers. It also has various colors depending on the melanin quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared to EMR, ESD could more effectively treat early-stage AMM. Indeed, ESD was applied to a few cases of esophageal malignant melanomas, and long-term survival was achieved in these cases[13,14]. However, to our knowledge, this is the first case of ESD for AMM.…”
Section: Discussionmentioning
confidence: 99%